Tu Youyou：A scientist moving forward in controversy - Editor Group of Traditional Medicine Research (Traditional Medicine Research, 2019)
The 13th National People's Congress Standing Committee was held in Beijing on Sept. 17, 2019. President of China Xi Jinping signed a presidential decree to award individuals, national medals and honorary titles. Tu Youyou, the winner of the 2015 Nobel Prize in physiology or medicine, was awarded the Medal of the Republic [1]. As the winner of the 2015 Nobel Prize in physiology or medicine, Tu Youyou and her team, discovered that artemisinin and dihydroartemisinin could be used to treat malaria [2]. Although Tu Youyou won the Nobel Prize in 2015, she didn’t have a Ph.D. degree. In 2017, she did not been admitted to the Chinese Academy of Sciences again [3]. As early as Oct. 9, 2015, The New York Times reported, “Q. and A.: Tu Youyou on Being Awarded the Nobel Prize”: “Q: Are you disappointed not to have been admitted to the Chinese Academy of Sciences? A: I applied many times, because people told me I should. I did receive a few awards for the discovery. At the National Science Conference in 1978, my team was given an award. As the team leader, I accepted on behalf of the team. The Minister of Public Health personally recommended me for academy membership. However, many factors must come into play. It’s complicated [4].” Usually, the Nobel Prize is awarded to individuals only [5]. Research of artemisinins has been carried out since the early 1970s, by hundreds of scientists all together under the “whole nation" system. For example, Xu Liu of Guilin Pharmaceutical Company designed and synthesized dihydroartemisinin C10-monoesters of diacids [6]. “Tu was the first to show that this component, later called Artemisinin, was highly effective against the malaria parasite, both in infected animals and humans.”the Nobel Committee said [7]. In 2011, Tu Youyou was awarded by the Lasker Foundation. The Lasker Award is often seen as a precursor to the Nobel Prize. This event reignited a controversy over whether one person should be recognized for developing the drug. Some Chinese scientists even co-authored letters to the Nobel Committee, stating that "We would rather no-one have this Nobel Prize, rather than Tu Youyou have it alone [8, 9]." It is noted that Tu Youyou turned to ancient texts of Chinese medicine named Zhouhou Beiji Fang and discovered clues to identify and extract the active component of the Chinese herbal medicine Qinghao (Artemisia carvifolia Buch.-Ham. ex Roxb. Hort. Beng.). She then delivered her Nobel Lecture titled “Discovery of Artemisinin - A Gift from Traditional Chinese Medicine to the World” on Dec. 17, 2015 at Aula Medica, Karolinska Institutet in Stockholm [10]. This made traditional medical practitioners, especially Chinese medicine practitioners very excited as they hoped it would bring some positive publicity to usefulness of traditional medicine. However, the Prize motivation on official website is still just "for her discoveries concerning a novel therapy against Malaria [2]." On May 30, 2019, the latest research results of the Tu Youyou team were published on The New England Journal of Medicine titled A Temporizing Solution to “Artemisinin Resistance" [11]. In addition, the application for the "Clinical trial of dihydroartemisinin tablet in the treatment of systemic lupus erythematosus and discoid systemic lupus erythematosus" submitted by the Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences, where the Tu Youyou team is located, has been approved. Kunming Pharmaceuticals, Inc. is the responsible party [12].